Effects of Viscosity Variations on Buoyancy-Driven Flow from a Horizontal Circular Cylinder Immersed in Al2O3-Water Nanofluid - Mohammad Reza Habibi; Meysam Amini; Ali Arefmanesh; Esmaeil Ghasemikafrudi (Iranian Journal of Chemistry & Chemical Engineering, 2019)
The buoyancy-driven boundary-layer flow from a heated horizontal circular cylinder immersed in a water-based alumina (Al2O3) nanofluid is investigated using variable properties for nanofluid viscosity. Two different viscosity models are utilized to evaluate heat transfer enhancement from a cylinder. Exact analytic solutions of the problem are attained employing a novel powerful technique is known as the Optimal Homotopy Analysis Method (OHAM). The accuracy and reliability of the results are verified by comparing them with experimental results in the literature. It is found that the characteristics of flow and temperature distributions are significantly influenced by the volume fraction of alumina nanoparticles, as well as nanofluid viscosity models. Enhancing the volume fraction of nanoparticles, the surface shear stress and the local Nusselt number both increase in the middle regions of the cylinder. The results also indicated that with increasing the nanoparticles volume fraction, isotherms become less dense and the absolute values of the stream-function decrease within the domain. Based on the results of the parametric study, two correlations (based on two different effective viscosity models) are proposed for the average Nusselt number of the alumina-water nanofluid in terms of volume fraction of the nanoparticles and the Rayleigh number which can be used as benchmarks for future investigations. However, uncertainties of viscosity models showed different manners on heat transfer coefficient versus nanoparticles volume fraction.